Can Israel prevent the ICC from conducting an investigation in the situation in Palestine? - Jahan, Ramisa (Penerbit Universiti Kebangsaan Malaysia, 2022)
The territorial conflict between Israel and Palestine has been the longest dispute in history. Although various efforts have been made to reconcile the dispute, no successful outcome could be achieved. The tension between the two states have been ever-increasing and upon the completion of preliminary examination, the ICC has now declared to conduct an investigation into the Palestinian situation. However, there has been speculations regarding the ICC’s ability to conduct an investigation on the basis of various clauses in the Rome Statute. Moreover, upon the declaration of an investigation by the OTP, the Israeli government has condemned the decision on various grounds. The primary objective of this paper is to iterate that Palestine is a recognized state and the crimes being committed in its territories fall under the purview of the Rome Statute, entailing accountability of the perpetrators. Hence, the author has attempted to refute Israel’s grounds and basis for non-cooperation and analyses the alleged “escape-clauses” in the Rome Statute. Finally, the author has reinforced that the ICC plays a non-partisan role in conducting investigations and holding war criminals accountable. Furthermore, the so-called “escape-clauses” in the Rome Statute are not loopholes rather a means by which the ICC aims to encourage national courts to undertake genuine proceedings to prosecute war criminals, in order to ensure global peace and order. Therefore, international law cannot be used as a tool to escape liability. The author has applied qualitative method, relying on primary and secondary sources of international law.